Interakcije med zdravili za starostnike-teoretičen in praktičen vidik - Tršinar, Mihaela (Farmacevtski vestnik, 2005)
The incidence of diseases increases with age, consequently the consumption of drugs is significantly higher in elderly than in other populations. Polytherapy, pharmacokinetic and pharmacodinamic alternations in elderly are probably one of the major factors that place the elderly population at higher risk of developing clinically significant drug-drug interactions. Pharmacokinetic drug interactions can occur at all pharmacokinetical levels, however the most of them appear at the drug metabolism and excretion level because of the impairments of both levels in elderly. On the other hand, pharmacodinamic drug interactions occure when two or more used drugs have synergistic or antagonistic pharmacological activities. The most frequent and dangerous reported drug-drug interactions in elderly include combinations of warfarin and nonsteroidal anti-inflammatory drugs, sulfonamides, macrolide antibiotics, quinolone antibiotics or phenytoinč combinations of angiotensin converting enzyme inhibitors and potassium supplements or spironolaconeč combinations of digoxin and amiodarone or verapamil and combinations of theophylline and quinolone antibiotics. Pharmaceutical intervention plays an important role in improvement of pharmacotherapy in elderly. The cooperation between pharmacist and physicians is one of the main key for improvement of pharmacotherapy in elderly.
Keywords: interakcije; jemanje zdravil; starostniki